The neuropathology of dementia - Esiri, Margaret M.; Lee, V. M.-Y; Trojanowski, John Q. (Cambridge University Press, 2004)
Completely rewritten and updated, this new edition is almost twice the size of its predecessor. Illustrated in colour throughout, and with contributions from the world's leading authorities, it is the definitive reference on the neuropathology of dementia. It gives practical guidance to pathologists, describes the contribution of neuroimaging to diagnosis, and surveys the clinical features of dementia. New material includes: • Three entirely new chapters on neuroimaging, molecular diagnostics, and transgenic models. • Two chapters on tauopathies under new authorship. • A chapter under new authorship on synucleinopathies, which includes multiple system atrophy. From reviews of the first edition: 'This up-to-date and authoritative account will be invaluable for practising neuropathologists and a treasured work of reference for psychiatrists and neuroscientists with an interest in dementia.' Nigel J. Cairns, International Journal of Geriatric Psychiatry ' ... this publication is a 'must have' for every practising neuropathologist.' Journal of Neuropathology and Experimental Neurology